The Indonesia Spice Up The World (ISUTW) Campaign As An Indonesian Nation Branding Effort: Kampanye Indonesia Spice Up The World (ISUTW) Sebagai Upaya Nation Branding Indonesia - Parmato, Diaz; Darman Moenir, Haiyyu; Elian Nasir, Putiviola (Palito, 2023)
The development of globalization throughout the world also affects the interaction between state actors in the international system, especially in the practice of diplomacy carried out by states. One form of diplomacy that has developed is the gastrodiplomacy campaign carried out by Indonesia. At the end of 2020, an Indonesia Spice Up the World (ISUTW) gastrodiplomacy campaign was initiated which was initiated by the government and across ministries in Indonesia with the aim of increasing exports of Indonesian spices and local culinary seasonings and expanding the network of Indonesian restaurants abroad as one of the efforts in Indonesia's national economic recovery after the Covid-19 pandemic. The purpose jncarried out by Indonesia through the Indonesia Spice Up the World (ISUTW) campaign. Gastrodiplomacy campaigns carried out by a country can be analyzed through nation branding strategies in seeing how the strategy can achieve a country's national interests. The research was conducted using the conceptual framework of "Nation Branding" from Juyan Zhang. Data collection techniques and data analysis are carried out by qualitative methods and descriptive analysis. The research conducted found that Indonesia with the ISUTW gastrodiplomacy campaign has carried out a nation branding strategy through six nation branding strategies proposed by Juyan Zhang including, product marketing strategy, food event strategy, coalition-building strategy, use of opinion leaders, education strategy and Media Relation Strategy. The six strategies in the nation branding effort in the gastrodiplomacy campaign help Indonesia to achieve Indonesia's national interests in terms of the national economy and culinary promotions carried out